Smartphone-based solution for pedestrian detection and communication with a driver assistance system - Sousa, Pedro (2022)
This paper presents an on-going project that consists of a smartphone-based solution for detecting pedestrians in crosswalks and communicating that information for a driver assistance system. The solution assumes a pedestrian using a smartphone, beacons in traffic lights and a driver with an android app, both apps communicating with a central database. The pedestrian app warns the user of crosswalks nearby and notify drivers if crosswalks are approaching and also if there are people in it. We also present the on-going tests that are being carried out to conclude the usefulness of the system in a real.